THE CONTRIBUTION AND ROLE OF LANGUAGE CENTERS IN ACTUALIZING WORLD-CLASS UNIVERSITY - Hamid, M. Abdul; Fatimah, Siti; Charis, M. Abdullah (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2022)
This study aimed to investigate the contribution and role of Language Centers in actualizing World-Class University within the State Islamic Higher Education (PTKIN). This research was a case study using qualitative approach. The subjects were two Language Centers located at UIN Syarif Hidayatullah Jakarta and UIN Maulana Malik Ibrahim Malang. In collecting data, researchers conducted interviews and documentation. The data collected were analyzed through data reduction, presentation, and conclusion. The results showed that the contribution and role of the Language Centers were very significant in supporting the actualization of World-Class University. Both Language Centers have contributed to a) improve/increase foreign language skills, b) detect language skills, c) archive important translated documents, and d) organizing language-related training or workshops. They had a role in building a global university brand through international cooperation, seminars or conferences, and sending lecturers to Al-Azhar University in Egypt to introduce the Indonesian language and culture. Abstrak: Penelitian ini bertujuan untuk mengetahui kontribusi dan peran Pusat Pengembangan Bahasa dalam mewujudkan World Class University di lingkungan PTKIN. Penelitian ini merupakan studi kasus dengan menggunakan pendekatan kualitatif. Ada dua Pusat Bahasa yang menjadi subjek penelitian yaitu yang berlokasi di UIN Syarif Hidayatullah Jakarta dan Maulana Malik Ibrahim Malang. Dalam pengumpulan data, peneliti melakukan wawancara dan dokumentasi. Data yang terkumpul dianalisis dengan cara reduksi data, sajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kontribusi dan peran Pusat Pengembangan Bahasa sangat signifikan dalam mendukung terwujudnya WCU. Kedua Pusat Bahasa telah memberikan kontribusi dalam: a) peningkatan kemampuan berbahasa asing, b) mendeteksi kemampuan berbahasa, c) mendokumentasikan dokumen-dokumen terjemahan penting, dan d) menyelenggarakan pelatihan atau workshop terkait bahasa. Sedangkan peran keduanya di antaranya membangun global brand universitas melalui kerja sama internasional, seminar atau konferensi, dan pengiriman dosen ke Universitas Al-Azhar di Mesir untuk memperkenalkan bahasa dan budaya Indonesia.